Management and Handling of Patient Pain in the Ebony Room of Tora Belo Hospital, Sigi Regency - Jumain; Wahyu; Lexy Kareba; Agustinus Talindong; Parmi (J.Abdimas: Community Health, 2023)
Pain is an unpleasant experience because it causes emotional, sensory damage and even tissue damage. Pain is sometimes termed as destructive, it can be described as a feeling such as burning, emotion, fear, nausea, a feeling of being stabbed. Pain is generally accompanied by a feeling of anxiety and a very strong desire to escape from the pain that is felt. Moreover, every feeling of pain with moderate to strong intensity is accompanied by a feeling of anxiety and a strong desire to escape from the pain experienced. Cases of pain are quite common, especially in postoperative cases, injuries, ulcer disease, cases of traffic accidents or accidents in the work environment and others. Preventive actions in the form of promotive and preventive accompanied by pain management and management are a priority. This service aims to be able to provide knowledge and understanding in terms of pain management in the Ebony room of Tora Belo Hospital, Sigi Regency. This counseling program was carried out in the Eboni room in January 2023 in the form of lectures, questions and answers and pain measurements in patients and simulations of implementing pain management. This counseling is running actively, the patient and the patient's family are very enthusiastic about listening and asking various things related to pain management that are not yet understood. Counseling given to patients is considered very effective and appropriate, thus helping patients to reduce the pain they feel. Suggestions for the next activity are to make more use of social media so that the dissemination of information is wider.